Population dynamics of Characidium lauroi and C. alipioi (Teleostei, Crenuchidae) in the Ribeirão Grande microbasin, eastern Serra da Mantiqueira, São Paulo State - DOI: 10.4025/actascibiolsci.v29i3.481 - Braga, Francisco Manoel de Souza (2007)
In low-order streams, the high and variable water flow rates offer both advantages and disadvantages to the life cycle of fishes. Even closely related species living in similar habitats can show differences in life history patterns. Based on oocyte-size distributions, C. lauroi was classified into the fractional spawning type, and C. alipioi into the total spawning type. The absolute fecundity of C. lauroi ranged from 1,313 to 2,925 oocytes; in C. alipioi the absolute fecundity ranged from 2,213 to 25,550 oocytes. The nonparametric Spearman correlation test showed statistical significance between the gonadosomatic index and fecundity for both species. The growth parameters, natural mortality rate and survival rate for females of C. lauroi were: K = 0.68 yr-1, Loo = 8.7 cm, tmax = 4.4 years, M = 1.62 yr-1, S = 19.79%, and for males: K = 0.78 yr-1, Loo = 6.9 cm, tmax = 3.8 years, M = 1.89 yr-1, S = 15.11%. The growth parameters, natural mortality rate and survival rate for females of C. alipioi were: K = 0.90 yr-1, Loo= 12.2 cm, tmax = 3.3 years, M = 1.81 yr-1, S = 16.37%, and for males: K = 0.76 yr-1, Loo = 10.1 cm, tmax = 3.9 years, M = 1.71 yr-1, S = 18.10%.